Membangun Kemandirian Ekonomi Masyarakat dengan Bank Sampah - Agus Sriyanto; Nora Adira Brabo; Ifan Haryanto; Arif Nur Hidayat; Iis Torisa Utami (Lembaga Pengembangan Kinerja Dosen, 2025)
Strategy to build public awareness so that they can be 'friends' with waste to get direct economic benefits from waste. Waste banks cannot stand alone but must be integrated with the 4R movement (recycle, reuse, reduce, and replace), namely the activity of treating waste by reusing, reducing, recycling, and replacing so that the direct benefits felt are not only economic, but also the development of a clean, green and healthy environment. In this activity, collaboration with existing waste banks in the environment so that the results are more optimal. The result is good enthusiasm from the community so that this activity runs according to plan.